„Nielokalność mechaniki kwantowej” kontra „Samobójstwo dla nauki” – różnice stylu naukowego i popularnonaukowego (Conversatoria Linguistica, 2018)
In my work I compare differences between language of theoretical science and popular science. I have analyzed the most important features and realisation ways of those styles. To do so, I have presented two samples – one theoretical science and one popular science. Both of them refer to the same field – quantum mechanics. Both of them present scientific discoveries, but there is a difference in way of doing it and this is the main subject i focus on in this article.